Peran dan hambatan efektifitas financial technology Baitul Maal wa Tamwil di Indonesia - Gunawan, Risma (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the role and obstacles to the effectiveness of Baitul Maal wat Tamwil’s Financial Technology in Indonesia. This research is qualitative research with the type of research used, namely the case study method. The data collection technique used in this research is evaluation and identification of articles, books and research journals. The object of this research is BMT UGT Sidogiri Pasuruan, East Java. The research results show that there are roles and obstacles when BMT UGT Sidogiri implements Fintech in its services, including Fintech making transactions easier for its members, but many of them are still unfamiliar with technology and this is one of the obstacles for BMT itself.